Rehabilitation of patients with paraplegia - a review of the diversity of forms - Krakowska, Natalia; Szmelcer, Beniamin Piotr; Zaborna, Daria; Fortuna, Aleksandra; Wszelaki, Patrycja; Florczak, Aleksander; Wilczyński, Michał; Ciepłuch, Justyna; Skierkowska, Natalia; Porada, Mateusz; Wąsicki, Mariusz; Modrzejewski, Mateusz; et al. (Journal of Education, Health and Sport, 2019)
Abstract:Background: Damage to the spinal cord most often occurs as a result of spine injury, often causing the disability. In every patient with paraplegia, complications may occur in the form of: sensory disorders, bedsores, contractures, urinary and stool incontinence, paresis or limb paralysis, as well as sexual problems.Material and methods: Analysis of available literature, articles in the Google Scholar and PubMed database using keywords: Rehabilitation, Paraplegia, NeurologyResults: Losing the function of locomotion and self-care in everyday activities is a great psychological burden, both for the sick person and his family. Rehabilitation proceeding should include physical, psychological and social aspects. For paraplegics, the introduction of early and appropriately targeted treatment may reduce the risk of onerous complications and allow for maximum self-empowerment in basic activities. For a person with disability, it is a chance to achieve self-acceptance and return to a dignified life in society.Conclusions: Problems of patients with paraplegia, despite the fact that they were described in many books and articles, should still be considered in studies that would use the latest news from the world of science. Patients struggling with this problem still expect further measures to improve their quality of life.